PENINGKATAN AKTIVITAS ENZIM SOD SERUM DAN KELUHAN KESEHATAN TERHADAP PAPARAN ASAP PEMBAKARAN KAYU PADA PEKERJA - Fitri Rokhmalia; Lilis Sulistyorini; Soedjajadi - (Jurnal Penelitian Kesehatan SUARA FORIKES, 2016)
The chronic exposure of nitrogen dioxide and formaldehyde gases effected cellular influence enzymes activity SOD. This study aim to analyze the effect of exposure to nitrogen dioxide and formaldehyde gases against SOD and health complaint of worker in home industry petis. The method of this study was analytical observation with prospective longitudinal study with design study cross-week. Research sites of home industry petis and government Sekardangan office. The population was 2 population that were the workers of home industry petis and the administration worker of government sekardangan office in Desa Sekardangan Kabupaten Sidoarjo with some criteria that worked at male, not getting sickness asma and willing to participate in this study. Sample size had 24 persons that was taken by simple random sampling, 12 persons from each workers home industry petis and administratif worker in government sekardangan office. The analysis result shown that nitrogen dioxide and formaldehyde gases in air effected of enzymes SOD difference before and after exposure working group and not exposed (p